Peran Sikap dan Inovasi Merek dalam Meningkatkan Ekuitas Merek pada Nasabah Bank Mandiri di Jakarta Barat - Raymond Cipto Aryananda; Richard Andrew (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to examine the effect of attitude and brand innovation on brand equity among Bank Mandiri Customers in West Jakarta. In the face of increasing competition in the banking industry, effective brand management is crucial for maintaining market position and enhancing customer loyalty. This research uses a quantitative approach by analyzing data from 100 respondents who are involved in transactions at Bank Mandiri. The data is analyzed using Structural Equation Modeling (SEM) to explore the relationships between variables. The findings show that both brand attitude and brand innovation have a significant positive effect on brand equity. Specifically, a positive brand innovation enhances perceptions of quality and the brand’s competitiveness in the market. This study provides practical implications for Bank Mandiri’s management in formulating more effective marketing strategies by considering these two factors. The research also emphasizes the importance of innovation that aligns with customer expectations in strengthening brand equity in the competitive banking market.